TRANSPORT GEOGRAFIYASIDA O‘RGANISH USULLARI - Niyazov, A.A. (SCIENCE and SOCIETY, 2024)
This article analyzes the issue of methodology in transport geography, examining general and specific research methods and their distinctive features. Additionally, it discusses the scientists who introduced these research methods to the field, focusing on important aspects of their approaches.
Keywords: methodology; statistical; mathematical modeling; cartographic; comparative analysis; geometric; cartographic digitization